Counterterrorism and Radical Eco-Groups: A Context for Exploring the Series Hazard Model - Carson, Jennifer Varriale (Journal of quantitative criminology, 2014)
Objective This study examines whether radical eco-groups have been deterred by legal sanctions. From a rational choice framework, I argue that members of these groups weigh costs and benefits. I measure an increase in costs, or an objective deterrence effect, through four federal sentencing acts targeted at reducing the criminal behavior of these groups [the tree-spiking clause of the Anti-Drug Abuse Act (ADA), the Animal Enterprise Protection Act (AEPA), the Anti-Terrorism and Effective Death Penalty Act (AEDPA), and the Animal Enterprise Terrorism Act (AETA)] and hypothesize that this legislation decreased the hazard of subsequent attacks. Methods This research is a quasi-experimental design utilizing the 1,068 illegal incidents perpetrated in the name of the environment, animal, or both as extracted from the Eco-Incidents Database. Using series hazard modeling, I examine the time until the next incident, serious incident, and ideologically specific incident in relation to dummy variables operationalizing the enactment dates of the above legislation. Results All in all, the results are somewhat consistent with a rational choice framework and my hypotheses. The ADA decreased the hazard of another attack (11 %) and environment-only attack (15 %), while at the same time increasing the hazard of a terrorist, damage, and animal-related attack. AETA decreased the hazard of all (47 %), damage (42 %), and the behavior it was aimed at, that of animal-only incidents (52 %). However, neither the AEPA, nor AEDPA had a significant effect on any of the outcomes. Conclusions Overall, radical eco-groups were deterred by legal sanctions, but these findings are legislation and outcome specific in addition to including displacement effects.